The Effectiveness of Cognitive Behavioral Therapy Using Cognitive Restructuring Techniques in Group Settings to Reduce Smoking Behavior in Adolescents - Sanjaya, I Putu Andika; Astuti, Kamsih (citeus, 2025)
There are numerous factors that drive adolescents to smoke, one of which is the presence of negative or irrational thoughts related to smoking behavior itself. Such thoughts include beliefs that smoking makes them appear more masculine, more accepted within their social circles, among other irrational perceptions. This study aims to evaluate the effectiveness of cognitive behavioral therapy (CBT) using cognitive restructuring techniques in a group setting to reduce smoking frequency in adolescents by addressing their irrational thought patterns. A quantitative experimental method was employed, using a pretest-posttest control group design. A total of 8 students were randomly assigned to two groups. Data analysis was conducted using parametric statistical tests, specifically the independent sample t-test and the correlated/paired sample t-test. The results indicate that cognitive restructuring techniques applied in group setting significantly reduce smoking behavior among adolescents.